Enhanced Decision Model for Optimize Operational Performance and Cost Efficiency Under Disc Interval-Valued Fermatean Fuzzy Acknowledge - Qiaosong Jing (IEEE Access)
Improving operational and cost effectiveness is crucial for enhancing organizational performance, competitiveness, and resilience. While traditional fuzzy-MCDM methods are widely used to handle uncertainty and imprecision, they often fall short in capturing the layered, hierarchical uncertainties inherent in real-world decision-making contexts. To address these limitations, we propose a novel methodology: Disc Interval-Valued Fermatean Fuzzy Sets (D-IVFFSs) integrated with a CRADIS-based MCDM technique. The disc-based and interval-valued structure of D-IVFFSs provides an enhanced capacity to model complex, nuanced uncertainties more flexibly and accurately than conventional fuzzy models. Additionally, the CRADIS method amplifies decision-making precision by incorporating multiple MADM approaches, optimizing the modelŠs adaptability to practical decision challenges. A case study demonstrates the modelŠs effectiveness in achieving operational stability and cost improvements, showcasing D-IVFFSŠs advanced capabilities for addressing uncertainties that traditional methods struggle to fully capture.